Dopamine Responsiveness in the Nucl. Accumbens Shell and Parameters of the Heroin-Influenced Conditioned Place Preference in Rats - Wang, Ch.; Chen, H.; Wang, X.; Zhang, R.; Hao, W. (Нейрофизиология, 2015)
Previous evidence demonstrated that drug-induced extracellular dopamine (DA) concentrations in the nucl. accumbens shell (AcbSh) might underlie different vulnerabilities to heroin addiction in inbred mice strains. We investigated a potential role of the responsiveness of the DA system in the AcbSh with respect to the vulnerability to heroin-influenced conditioned place preference (CPP) in rats. Animals were randomly assigned to the heroin and saline (control) groups. Heroin-group rats were then re-classified into two groups according to the degree of heroin-induced CPP, high preference (HP) and low-preference (LP) ones. The levels of extracellular DA and dihydroxyphenyl acetic acid (DOPAC) were estimated dynamically by in vivo microdialysis. Compared with the saline group, extracellular DA and DOPAC concentrations in the heroin-treated groups were significantly higher 30 min after the last injection, but the DA level decreased sharply in these groups on days 1 and 3 and became lower than that of the saline group. Compared with LP-group rats, HP-rats displayed a higher heroin-induced increase in the DA concentration 30 min after the last heroin injection and higher DOPAC and DOPAC/DA ratios 14 days after such injection. These results suggest that differences in the DA system responsiveness in the AcbSh may determine individual differences in vulnerability to heroin addiction.